Vibrational assignments, spectroscopic investigation (FT-IR and FT-Raman), NBO, MEP, HOMO‒LUMO analysis and intermolecular hydrogen bonding interactions of 7-fluoroisatin, 7-bromoisatin and 1-methylisatin ‒ A comparative study - Polat, Turgay; Bulut, Fatih; Arıcan, Ilknur; Kandemirli, Fatma; Yildirim, Gürcan (Elsevier BV, 2015)
Abstract In this comprehensive study, theoretical and experimental studies were carried out on 7-fluoroisatin, 7-bromoisatin and 1-methylisatin using FT-Raman and FT-IR spectra. The optimized geometrical parameters and theoretical vibrational frequencies were calculated by means of density functional theory (DFT/B3LYP) with 6–311++G(d,p) basis set based on scaled quantum mechanical (SQM) method for the first time. The relative abundances of the possible tautomers or conformers found were calculated with respect to the Boltzmann distribution. Moreover, the harmonic vibrational frequencies including IR and Raman intensities, thermodynamic and electronic parameters were computed in detail. The effects of substituents –F, ‒Br and –CH3 on the crucial characteristics pertaining to the title compound of isatin were investigated, and the obtained data were compared with each other. Natural bond orbital (NBO) analysis was applied to study the stability arising from charge delocalization along with the compound. The chemical reactivity parameters (chemical hardness and softness, electronegativity, chemical potential and electrophilicity index) were discussed clearly. The HOMO and LUMO energies determined showed that the serious charge transfer occurs in the title molecules studied. Furthermore, the size, shape, charge density distributions and chemical reactivity sites belonging to the molecules were obtained by mapping electron density isosurface with electrostatic potential surfaces (ESP). Additionally, the hydrogen-bonded complexes were simulated to describe the roles of intermolecular hydrogen bonding on the molecular structures and vibrational frequencies.
Keywords: Vibrational Spectra; Hydrogen Bonding; Fluoroisatin; Bromoisatin; DFT; Methylisatin; 3. Good health